A brief review of electrocatalytic reduction of CO2—Materials, reaction conditions, and devices. Issue 7 (21st June 2021) - Pei, Yuhou; Zhong, Heng; Jin, Fangming
Abstract: Global warming caused by the rapid increase in atmospheric CO2 concentration is regarded as one of the most serious problems faced by human being. Electrochemical CO2 reduction (ECR) is one promising strategy that can fix CO2 in a mild and clean manner combined with sustainable energies. However, the ECR performance is highly dependent on the catalysis system because of the difficulty in CO2 activation, low mass transfer, poor product selectivity, and competitive hydrogen evolution reaction (HER). The binding strength of electrocatalysts toward carbon intermediates is the crucial factor for ECR performance. Furthermore, the reaction conditions and the configurations of devices are also of significance for ECR efficiencies. Here, we briefly reviewed the effects of electrocatalyst materials, as well as the reaction conditions, coupled anodic reactions, and devices on the ECR. Moreover, challenges and some perspectives for large‐scale applications are included. Abstract : This is a brief review of the electrocatalytic reduction of carbon dioxide. We reviewed the aspects of material design, reaction conditions, and devices, etc, and the perspectives are also included.